Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1063/1.4896060
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic topology and flux rope evolution during non-linear tearing of 3D null point current sheets

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 64 publications
5
36
0
Order By: Relevance
“…The distance between these two nulls is d 1 i ; they live for a few ion gyration timesand are accompanied by strong currents and enhanced energy conversion. A spontaneous emergence of magnetic nulls was explained in terms of topological bifurcations by Wyper & Pontin (2014a). The interconnection between the emerged radial nulls is more complex than between the spiral nulls in a flux rope.…”
Section: Results: "Multiple Nulls"mentioning
confidence: 99%
See 1 more Smart Citation
“…The distance between these two nulls is d 1 i ; they live for a few ion gyration timesand are accompanied by strong currents and enhanced energy conversion. A spontaneous emergence of magnetic nulls was explained in terms of topological bifurcations by Wyper & Pontin (2014a). The interconnection between the emerged radial nulls is more complex than between the spiral nulls in a flux rope.…”
Section: Results: "Multiple Nulls"mentioning
confidence: 99%
“…Observations, however, have suggested that nulls often concentrate in clusters (Deng et al 2009;Wendel & Adrian 2013). Several 3D MHD simulations addressed multiple null points (Galsgaard & Nordlund 1997;Wyper & Pontin 2014a, 2014b. Notably, the last two publications hinted atthe dominating role of the spiral nulls in the models.…”
Section: Introductionmentioning
confidence: 99%
“…For q = +  22 , the outflows form a tapered spire (Figure 12(a)) that waves and undulates (see the online movie). This wave motion follows the onset of tearing in the breakout sheet, in which blobs of high-density plasma associated with small flux ropes are formed in and ejected from the sheet (Wyper & Pontin 2014b;. Plasma in the spire is ejected at around Figure 12(b).…”
Section: Breakoutmentioning
confidence: 99%
“…At higher grid resolution, these currents should become even more filamentary in structure and greater in strength, and could produce quasi-steady heating of the loop in the aftermath of the jet. In addition, it is known that 3D null-point current layers are explosively unstable to resistive tearing at high Lundquist numbers (Wyper & Pontin 2014a, 2014b. Attaining the requisite Lundquist-number threshold demands better resolution than the simulations undertaken in this work.…”
mentioning
confidence: 80%